Response to The Use of Liquid Organic Fertilizer on Vegetative Growth in Soybean Plants Black (Glycine Soja L. Merrill) with Two Different Cultivars - Ramayanti, Sri; Rahmadina, Rahmadina; Idami, Zahratul (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2024)
Soybean-based food business and population growth drive the increase in soybean consumption every year in Indonesia. Soybean varieties and liquid organic fertilizer applications can help overcome losses in soybean plant growth and productivity. This study used a randomized block design (RAK) with treatment consisting of 2 factors with 3 repetitions. Factor i liquid organic fertilizer (p), consists of 4 levels, namely: p0 = 0 ml, p1 = 20 ml, p2 = 40 ml, p3 = 60 ml. the 2nd factor cultivar (k), consists of 2 types, namely: k1 = cultivar detam 1, k2 = cultivar detam 3. The results showed that the response and effectiveness of the application of soybean peel poc and different cultivars did not significantly affect the vegetative growth of black soybean plants, but when viewed as a whole p3 (60 ml) gave the highest value on the parameters of leaf area index 21 hst, root nodules, chlorophyll a, and chlorophyll b content.